2003
DOI: 10.1200/jco.2003.12.142
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Multicenter Trial on the Antiproliferative Effect of Lanreotide, Interferon Alfa, and Their Combination for Therapy of Metastatic Neuroendocrine Gastroenteropancreatic Tumors—The International Lanreotide and Interferon Alfa Study Group

Abstract: This prospective, randomized, multicenter study shows for the first time that somatostatin analogs, interferon alfa, or the combination of the two had comparable antiproliferative effects in the treatment of metastatic neuroendocrine gastroenteropancreatic tumors. Response rates were lower compared with those published in previous, nonrandomized studies. The antiproliferative effect of the tested substances was similar for functional and nonfunctional neuroendocrine tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
252
1
24

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(282 citation statements)
references
References 29 publications
5
252
1
24
Order By: Relevance
“…Significantly better 5-year survival rates have been reported from single centers after active interventions (Wängberg et al 1996, Sarmiento & Que 2003. The only curative treatment is radical surgery, but for palliation of symptoms the treatment can include cytoreductive surgery, ischaemic treatment of liver metastases or medical therapy with somatostatin analogues sometimes combined with interferon a (Kvols et al 1986, Faiss et al 2003, Kölby et al 2003, Roche et al 2003, Osborne et al 2006. Recently, somatostatin receptormediated radiotherapy has been introduced as palliative treatment (Kwekkeboom et al 2005(Kwekkeboom et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly better 5-year survival rates have been reported from single centers after active interventions (Wängberg et al 1996, Sarmiento & Que 2003. The only curative treatment is radical surgery, but for palliation of symptoms the treatment can include cytoreductive surgery, ischaemic treatment of liver metastases or medical therapy with somatostatin analogues sometimes combined with interferon a (Kvols et al 1986, Faiss et al 2003, Kölby et al 2003, Roche et al 2003, Osborne et al 2006. Recently, somatostatin receptormediated radiotherapy has been introduced as palliative treatment (Kwekkeboom et al 2005(Kwekkeboom et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a risk of hepatotoxicity, autoimmune disorders and the development of neutralizing antibodies. It is useful to note that in a recent prospective randomized trial using interferonalpha alone, somatostatin analogue alone, or the combination showed no additional benefit of the combination over the monotherapies (Faiss et al 2003).…”
Section: Interferon-alpha and Chemotherapy For Gut Neuroendocrine Tummentioning
confidence: 99%
“…Several subsequent phase II studies of recombinant interferon-alpha-2a, alone or in combination with 5-fluorouracil, reported symptomatic improvement and variable response rates in patients with NETs [49 -51]. Combination studies of interferon-alpha plus a somatostatin analogue as compared to somatostatin analogue monotherapy have shown response rates of 5%-6% with one of three studies favoring an improved overall survival with combination therapy [52][53][54]. In each of these studies, carcinoids and PNETs were evaluated together.…”
Section: Interferonmentioning
confidence: 99%